Sulfinylation on Superoxide Dismutase 1 Cys111: Novel Mechanism for 1‐Nitropyrene to Promote Acute Reactive Oxygen Species Generation. Issue 3 (21st January 2021) - Xie, Guangshan; Zhu, Lin; Zhang, Yanhao; Song, Yuanyuan; Zhang, Hongna; Yang, Zhu; Cai, Zongwei
Abstract : 1‐Nitropyrene (1‐NP) is one of the most representative diesel exhaust‐sourced components existing in fine particulate matter (PM2.5) and a potential carcinogen. 1‐NP demonstrates a significant higher cytotoxicity than its structural analogs and precursor. Herein, 1‐NP with its structural analog 3‐nitrofluoranthene and precursor pyrene in human lung epithelial cell lines are compared. An acute reactive oxygen species (ROS) accompanied with cell death is observed for 1‐NP. Using compound‐centric redox proteomics analysis, it is shown that 1‐NP significantly remodeled the redox proteome and specifically targeted on ROS reduction pathway. Superoxide dismutase 1 (SOD1) is identified as a potential target. It is demonstrated that 1‐NP directly acts on cysteine residue Cys111 and inhibits SOD activity. The position of nitroxide determines its direct target and contributes to the unique mechanism of 1‐NP. A novel mechanism for 1‐NP cytotoxicity and ROS induction is therefore proposed. Abstract : SOD1 is identified as a potential target of 1‐nitropyrene (1‐NP)‐induced cytotoxicity and reactive oxygen species (ROS) surge using compound‐centric redox proteomics analysis. Mass spectrometry (MS) data indicate that 1‐NP can directly attack SOD1 cysteine residue Cys111 to inhibit SOD activity and ultimately result in increased ROS production. A new mechanism of 1‐NP induced cytotoxicity and ROS generation is therefore proposed.